(untitled) (Scientific journal of the Fergana State University, 2025)
The article analyzes the importance of journalists’ written and oral speech culture in shaping public opinion. Following the rules of linguistics is essential for the correct and effective use of speech, and it plays a vital role in solving creative and professional problems. This article covers the forms of speech in the press, radio, television, and the internet, as well as the issues related to their correct and effective application. A journalist’s speech culture influences not only their professional success but also contributes to the moral and cultural development of society.